Administrating the Implantation of Distributing Equal Efforts between Teaching and Research within the Faculty Member - Shindi, Sanaa (International Journal of Psychosocial Rehabilitation, 2020)
There is a unanimous agreement that scientific research in general and, in higher education institutions specifically, has an excessive prominence. It is often considered the cornerstone of scientific progress and scientific inventions. Believing in its active role in the process of development in all its forms and fields, some Iraqi universities have begun to teach the scientific research approach in various faculties as a basic subject in most specialties.This paper presents a study of Iraqi universities, and the findings are based on a questionnaire of 55 faculty members. The results of the study could contribute to the discussion about the educational and strategic goals in the educational policy that must be accompanied by integrated preparation in all aspects of scientific and educational management, teaching, curricula, and teaching methods. The aim is to form a real scientific environment through the policy of teaching the culture of scientific research as a gradual process that begins with basic education by writing scientific reports and working on the method of criticism, scrutiny, and analysis. Eventually, the student will be able to deal with scientific research easily.